Ação de óleos essenciais sobre Colletotrichum gloeosporioides (Penz)do maracujazeiro-amarelo - Cesar Fernandes Aquino (2011)
The culture of maracujazeiro is important in the northern region of Minas Gerais, for being responsiblefor the aggregation of income for many family farmers. This culture shows considerable range ofdiseases, forcing producers to use increasing doses of fungicides. To try to alleviate these problems, itshould seek the alternative control of diseases. Thus the exploitation of the antimicrobial activity of plantsecondary compounds, may to constitute a potential way to alternative control of diseases in thisculture. The objective of this research was to investigate the action of essential oils from Lippiasidoides, Cymbopogon citratus and Ocimum gratissimum on Colletotrichum gloeosporioides of themaracujazeiro-amarelo. In the first phase of the research were conducted trials in order to investigatethe chemical composition of each essential oil and evaluate the fungitoxic and fungistatic action ofthese on the fungus C. gloeosporioides. The oils were analyzed by chromatography, in gas phase,coupled with mass spectrometry, and the antifungal activity was evaluated in a completely randomizeddesign in factorial scheme 5x3, being five concentrations (0, 1, 3, 5 and 7L mL-1) x essential oils ofthree medicinal species, with four replications. The thymol (30.24%), the isomers E and Z-citral(77.74%) and eugenol (92.89%) were chemical compounds with the highest percentage found for L.sidoides, C. citratus and O. gratissimum, respectively. It was verified that the essential oil of C. citratusproportioned the highest inhibition of growth mycelial at all concentrations tested. The other oils did notdiffer, except from the concentration of 5L mL-1, in which the oil of L. sidoides was more efficient thanthe oil of O. gratissimum. In production and germination of conidial, the oil of C. citratus was superior tooils of L. sidoides and O. gratissimum, in concentrations of 1 and 3L mL-1, inhibiting completely theproduction and germination, from the concentration of 3L mL-1. We observe a decrease in these, asthe concentrations of oil were increased. The essential oils used have fungitoxic and fungistatic effect,suggesting that thymol, citral and eugenol are the responsible for the observed activity. In the secondphase, the trials had as objective to evaluate two methods of inoculation of C. gloeosporioides inpassion fruit, to test the pathogenicity of different isolates, as well as the fungitoxic effect ofconcentrations of the oil of these plants on the fungus in treatment of the fruits. It was set a trail up incompletely randomized design to evaluate the pathogenicity of six isolates (Iso 1, Iso 2, Iso 3, Iso 4, Iso5 and Iso 6) of the fungus, with six replications. The second trial was conducted in a completelyrandomized design and factorial scheme 2x2, with two inoculation methods (suspension of conidia anddisc of mycelium ) and two stages of development of the fruits (green and ripe) with six replications. Thecontrols constituted of fruits inoculated only with sterilized water and inoculated fruits with discs of BDA.The antifungal activity of essential oils in the treatment of the fruits used the completely randomizeddesign in factorial scheme 5x3+1, being five concentrations (0, 2, 4, 6 and 8L mL-1) and threeessential oils, plus the treatment with fungicide (tebuconazole), with five replications. It was made thechemical characterization of oils by gas chromatography with mass spectrometry. All isolates werepathogenic, being the isolated 1 the most aggressive, followed by isolates 2 and 3. The ripe fruitshowed the largest diameters of lesions when inoculated with conidial suspension. In the treatment ofthe fruits, the oil of C. citratus proportioned the smallest diameter of the lesions until the concentrationof 6L mL-1, differing from the other oils tested. The oils of L. sidoides and O. gratissimum did not differamong themselves. In the concentration of 8L mL-1, all the oils inhibited the fungal growth. There wasa decrease in the diameter of the lesions, as it increased the concentrations of oils. The oil of C. citratusshowed higher fungicidal effect in controlling of C. gloeosporioides in the fruits. The oils of L. sidoidesand O. gratissimum are efficient from the concentration of 8L mL-1. It is concluded, the oil of C. citratuspresented fungitoxic effect superior to other oils, for all analyzed variables.